Marketing for Hospitality and Tourism / Third Edition - Bowen John; Kotler Philip; Makens James (Prentice Hall, 2002)
An indispensable guide to successful Marketing in the Hospitality Industry. Preface, Introduction: Marketing for Hospitality and Tourism, Service Characteristics of Hospitality and Tourism Marketing, The Role of Marketing in Strategic Planning, The Marketing Environment, Marketing Information Systems and Marketing Research, Consumer Markets and Consumer Buying Behavior, Organizational Buyer Behavior of Group Market, Market Segmentation and Targeting and Positioning, Designing and Managing Products, Internal Marketing, Building Customer Loyalty Through Quality, Pricing Products: Pricing Considerations and Approaches and Strategy, Distribution Channels, Promoting Products: Communication and Promotion Policy and Advertising, Promoting Products: Public Relations and Sales Promotion, Electronic Marketing: Internet Marketing and Database Marketing and Direct Marketing, Professional Sales, Destination Marketing, Next Year's Marketing Plan, Case Studies, Glossary, Index.